Impact of Neoadjuvant Chemoradiation on Pathologic Response in Patients With Localized Pancreatic Cancer - Wittmann, David; Hall, William A.; Christians, Kathleen K.; Barnes, Chad A.; Jariwalla, Neil R.; Aldakkak, Mohammed; Clarke, Callisia N.; George, Ben; Ritch, Paul S.; Riese, Matthew; Khan, Abdul H.; Kulkarni, Naveen; et al. (Frontiers in Oncology, 2020)
Introduction/Background: Multimodal neoadjuvant therapy has resulted in increased rates of histologic response in pancreatic tumors and adjacent lymph nodes. The biologic significance of the collective response in the primary tumor and lymph nodes is not understood. Methods: Patients with localized PC who received neoadjuvant therapy and surgery with histologic assessment of the primary tumor and local-regional lymph nodes were included. Histopathologic response was classified using the modified Ryan score as follows: no viable cancer cells (CR), rare groups of cancer cells (nCR), residual cancer with evident tumor regression (PR), and extensive residual cancer with no evident tumor regression (NR). Nodal status was defined by number of lymph nodes (LN) with tumor metastases: N0 (0 LN), N1 (1-3), N2 (>4). Results: Of 341 patients with localized PC who received neoadjuvant therapy and surgery, 107 (31%) received chemoradiation alone, 44 (13%) received chemotherapy alone, and 190 (56%) received chemotherapy and chemoradiation. Histopathologic response consisted of 15 (4%) CRs, 59 (17%) nCRs, 188 (55%) PRs, and 79 (23%) NRs. Patients who received chemotherapy alone had the worst responses (n=21 for NR, 48%) as compared to patients who received chemoradiation alone (n=25 for NR, 24%) or patients who received both therapies (n=33 for NR, 17%) (Table1; p=0.001). Median overall survival for all 341 patients was 39 months; OS by histopathologic subtype was not reached (CR), 49 months (nCR), 38 months (PR), and 34 months (NR), respectively (p=0.004). Of the 341 patients, 208 (61%) had N0 disease, 97 (28%) had N1 disease, and 36 (11%) had N2 disease. In an adjusted hazards model, modified Ryan Score of PR or NR (HR:1.71; 95%CI:1.15-2.54; p =0.008) and N1 (HR:1.42; 95%CI:1.1.02-2.01; p=0.04), or N2 disease (HR:2.54, 95%CI:1.64-3.93; p<0.001) were associated with increased risk of death. Conclusions: Neoadjuvant chemotherapy alone is associated with lower rates of pathologic response. Patients with CR or nCR have a significantly improved OS as compared to patients with PR or NR. Nodal status is the most important pathologic prognostic factor. Neoadjuvant chemoradiation may be an important driver of pathologic response.